Current treatment of war wounds. Evolution of the concept of the biological mechanism of antiseptics - Bello, Eduardo (1918)
The new guidelines that the current universal conflagration printed the treatment of wounds from firearms, should be considered definitive acquisitions; and reveal recent articles by Professor Moynihan, as well known for his many scientific papers and his famous treatise abdominal surgery. Along these lines, we will try to condense the ideas of this surgeon and all who have excelled in the immense task of pointing out new directions, to cement ideas, to destroy prejudice, made the big step forward in war surgery. We moved even more to address this issue, the memory always live on one of us, from the cruel anguish stirred our spirits at the powerlessness of our resources to overcome the infection in the wounded of our fratricidal war of 1895, in which surgeons who were responsible for the treatment of the victims of this massive civil strife painfully were surprised by the enormous perseverance and force of infection of wounds and bitter was his disappointment at the failure of his old ways, so many flattering wins he had conquered them in civil practice and then unfortunately proved inadequate and useless.